The mechanistic effects of human digestion on magnesium oxide nanoparticles: implications for probiotics Lacticaseibacillus rhamnosus GG and Bifidobacterium bifidum VPI 1124. Issue 12 (16th November 2022) - García-Rodríguez, Alba; Stillwell, Allayah A.; Tochilovsky, Blake V.; Tanzman, Jacob V.; Limage, Rhodesherdeline; Kolba, Nikolai; Tako, Elad; Marques, Cláudia N. H.; Mahler, Gretchen J.
Abstract : Ingested dietary MgO-NPs could form different magnesium aggregates that would reach the small intestine and interact with the gut microbiota. Abstract : The effects of nanoparticles (NPs) on human gut microbiota are of high interest due to the link between gut homeostasis and overall human health. The human intake of metal oxide NPs has increased due to their use in the food industry as food additives. Specifically, magnesium oxide nanoparticles (MgO-NPs) have been described as antimicrobial and antibiofilm. Therefore, in this work we investigated the effects of the food additive MgO-NPs on the probiotic and commensal Gram-positive Lacticaseibacillus rhamnosus GG and Bifidobacterium bifidum VPI 1124 . The physicochemical characterization showed that food additive MgO is formed by nanoparticles (MgO-NPs) and after simulated digestion, MgO-NPs partially dissociate into Mg 2+ . Moreover, nanoparticulate structures containing magnesium were found embedded in organic material. Exposure to MgO-NPs for 4 and 24 hours increased the bacterial viability of both L. rhamnosus and B. bifidum when in biofilms but not when as planktonic cells. High doses of MgO-NPs significantly stimulated the biofilm development of L. rhamnosus, but not B. bifidum . It is likely that the effects are primarily due to the presence of ionic Mg 2+ . Evidence from the NP characterization indicates that interactions of bacteria/NPs are unfavorable as both structures are negatively charged, which would create repulsive forces.